2014
DOI: 10.1016/j.proeng.2014.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conservation Agriculture on Maize-based Farming System in the Mid-hills of Nepal

Abstract: Conservation agriculture (CA) systems composed of intercropping and strip tillage practices were evaluated on marginalized maize-based farming system in hill region of Nepal. On-farm experimental trials were conducted on the field of 25 smallholder farmers in three villages of central mid-hill region. Results indicated that although CA systems did not increase crop yields; higher return and revenue were generated due to increased number of crop harvests and higher price of the cash crops used in intercropping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Research is needed to elucidate the potential constraints and opportunities for CA adoption in the region. Indeed, Paudyal et al (2001) previously recommended that zeroand minimum-tillage cropping systems research should be investigated in the maize-based systems of the midhills, but only a few such studies exist (Atreya et al, 2006;Paudel et al, 2014). In this study, we hypothesize that (i) soil physical properties between CA vs. CP will not differ within the first 2 yr after CA adoption, (ii) CA managed monsoon maize will not be more productive than CP within the first 2 yr after CA adoption, (iii) CA managed dry-season wheat and rapeseed will be more productive than CP within the first 2 yr after CA adoption, and (iv) earlier planting dates will improve productivity of wheat.…”
Section: Core Ideasmentioning
confidence: 99%
“…Research is needed to elucidate the potential constraints and opportunities for CA adoption in the region. Indeed, Paudyal et al (2001) previously recommended that zeroand minimum-tillage cropping systems research should be investigated in the maize-based systems of the midhills, but only a few such studies exist (Atreya et al, 2006;Paudel et al, 2014). In this study, we hypothesize that (i) soil physical properties between CA vs. CP will not differ within the first 2 yr after CA adoption, (ii) CA managed monsoon maize will not be more productive than CP within the first 2 yr after CA adoption, (iii) CA managed dry-season wheat and rapeseed will be more productive than CP within the first 2 yr after CA adoption, and (iv) earlier planting dates will improve productivity of wheat.…”
Section: Core Ideasmentioning
confidence: 99%
“…Various previous studies have reported that diverse organic farming practices applied in cereal crops have resulted in improved soil condition and enhanced crop yield particularly in hilly terrains (Roy et al 2010;Kumar Choudhary and Suri 2014;Paudel et al 2014;Pampuro et al 2017). Even different organic forms of compost impart distinct soil quality characteristics based on either particle size or composting methods adopted, such as reported by authors in compost prepared from pig slurry incorporated with saw dust, wood chips, and wheat straw (Romano et al 2014;Pampuro et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By 2050, agricultural food production is projected to increase by seventy percent globally to sustain food security for the growing population [1]. Limited scope in further expansion of global farmland area necessitates the adoption of effective conservation practices for sustainable intensification of food production [2,3]. Conservation tillage is well-recognized as a potential strategy to increase the agricultural sustainability by preserving soil and water resources and improving the production economy, among other agroecosystem services [4].…”
Section: Introductionmentioning
confidence: 99%